2006
DOI: 10.1111/j.1572-0241.2006.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Colonoscopic Cecal Intubation: An Analysis of 6 Years of Continuous Practice at a University Hospital

Abstract: Our analysis revealed cecal intubation and documentation rates that meet current guidelines, and identified factors that may cause substantial variance in these rates depending on the nature of the practice. The present analysis confirms that computerized databases can be used to assess individual and group cecal intubation and documentation rates on an annual basis, and to make these data available to the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 26 publications
6
104
2
Order By: Relevance
“…Colonoscopy success depends on three factors (12): (1) endoscopist related, experience and skill; (2) patient related, vital findings during procedure, colonoscopy reason, gender, BMI, previous abdominal surgery, radiotherapy, and situation of bowel cleansing; (3) technique related, sedation technique used and colonoscopy device. In a study conducted by Aslina et al (13), it was found that the rate of reaching the cecum in females (92.7%) was lower than that in males (95.5%). As for the study by Anderson et al (14), it was determined that gender was not a factor related to failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonoscopy success depends on three factors (12): (1) endoscopist related, experience and skill; (2) patient related, vital findings during procedure, colonoscopy reason, gender, BMI, previous abdominal surgery, radiotherapy, and situation of bowel cleansing; (3) technique related, sedation technique used and colonoscopy device. In a study conducted by Aslina et al (13), it was found that the rate of reaching the cecum in females (92.7%) was lower than that in males (95.5%). As for the study by Anderson et al (14), it was determined that gender was not a factor related to failure.…”
Section: Discussionmentioning
confidence: 99%
“…American Cancer Society Colorectal Cancer Task Force determined the standard criteria of cecum intubation success as 90% and set 95% goal as the ideal rate. Rates of reaching the cecum in important centers in United States were found to be 96%-100% (13). Colonoscopy success depends on three factors (12): (1) endoscopist related, experience and skill; (2) patient related, vital findings during procedure, colonoscopy reason, gender, BMI, previous abdominal surgery, radiotherapy, and situation of bowel cleansing; (3) technique related, sedation technique used and colonoscopy device.…”
Section: Discussionmentioning
confidence: 99%
“…The only unscheduled one is unsedated colonoscopy offered to patients who drink the purge solution and arrives without an escort and do not mind having the colonoscopy done without sedation. In VA 21 and community 22 practice settings this option has been provided to 1-2% of colonoscopy patients. Scheduled options include deep sedation, conscious sedation and unsedated colonoscopy.…”
mentioning
confidence: 99%
“…It is stated in the literature that the rate of accessing the cecum should be around 95% in academic centers (7). Aslinia et al (8) reported the success rate as 85.5% after evaluation of their colonoscopy results of 6 years. Yılmaz et al (1) stated their colonoscopic success rate as 78%.…”
Section: Discussionmentioning
confidence: 99%